Elaboração de rotinas de cálculo no software SMath studio: dimensionamento de sapatas rígidas e análise comparativa com os resultados processados pelo software AltoQi Eberick - NEVES, Gabriel de Carvalho (2023)
This work focuses on the design problem of reinforced concrete footings and the consequent verification of settlements, given that displacement calculation inaccuracies can lead to different unfavorable prognoses for the useful life of the structure. The proposed approach for method validation brings an alternative to the use of paid commercial software that dominates the structural design industry with the use of technological tools with open-source programs that describe the codes and functionalities. The free software SMath Studio was chosen to facilitate the presentation of the adopted equations and the elaboration of computational routines, being selected consolidated references in the area of geotechnics that allow a qualitatively varied spectrum on uses of the equations traditionally adopted in these calculations for applications in professional contexts, using the traditional Eberick software, developed by AltoQi, as a counterpoint. From the computational simulations developed, it was attested that the variation of responses presented satisfactory performance that guaranteed safe results from the calculation point of view, since the resistant stresses of the reinforcement exceed the values of the tensile efforts at the base of the shoe, as well as there is no crushing of the compression struts nor settlements greater than the limits adopted in the literature. The revision of the concepts for the development of the work allowed to insert learning that helps in the understanding of the phenomenon, significantly reduces the possibility of input errors and incorporates the formal knowledge to the iterative and incremental development, allowing for better design practices.